The vista system: a new bipolar resection device for endourological procedures: comparison with conventional resectoscope - Wendt-Nordahl, Gunnar; Häcker, Axel; Reich, Oliver; Djavan, Bob; Alken, Peter; Michel, Maurice Stephan (European urology, 2004)
Objective: - Conventional transurethral resection of the prostate (TURP) uses a monopolar electrocautery system in which the current passes from the active electrode through the patient's body towards the return plate and may cause distant negative effects. In this study a new developed resection device, the Vista system, using a bipolar electrocautery system and 0.9% sodium chloride solution for irrigation, was evaluated in an ex-vivo model. - Methods: - The modified model of the isolated blood perfused kidney was used to determine cutting qualities, ablation rate, blood loss and coagulation depth of the bipolar resectoscope. After ablating the renal tissue of a perfused kidney in a surface area, blood loss was semiquantitatively determined. Afterwards samples were taken and processed for histological evaluation of the coagulation depth. We compared the new bipolar resection device against a conventional monopolar resectoscope. - Results: - We found good cutting qualities of the bipolar resectoscope although it is more difficult to start a cut. The ablation rate is determined by the width of the electrode and is similar to the standard device (30cm2/min). The bleeding is reduced with increasing output powers (26.13 ± 6.15g/min (level 5); 20.49 ± 5,47g/min (level 6); 13.16 ± 5,47g/min (level 7); 10.43 ± 4.76g/min (level 8) and lower compared to a conventional monopolar resectoscope (17.08 ± 4.47g/min). The coagulation depth increases with higher output powers but is reduced compared to the standard device (118 ± 22μm (level 5); 121 ± 23μm (level 6); 141 ± 62μm (level 7); 163 ± 30μm (level 8) versus 287 ± 57 (monopolar resectoscope)). - Conclusion: - Our results with the bipolar resection device for TURP suggest that it may offer an alternative to conventional TURP. As active and the return electrode are placed on the resectoscope, high current densities are achieved locally and complications caused by distant negative effects of the current are theoretically reduced in vivo. Furthermore the risk of TUR syndrome is theoretically eliminated by using physiological sodium chloride solution for irrigation. To prove the clinical significance of our ex-vivo findings, clinical studies including large numbers of patients have to be performed.